Digestible Lysine Requirement for Hen Turkeys from 0 to 6 Weeks of Age - Thompson, K.A.; Blair, E.; Baker, K.A.; Firman, J.D. (International Journal of Poultry Science, 2004)
Two floor pen trials were conducted to determine the digestible lysine requirement of female turkeys from 4 to 15 and 29 to 40 days of age. For the 4 to 15 day period, 480 four-day-old poults were weighed, sorted, and assigned to a treatment with 10 poults per pen. For the 29 to 40 day experiment, 384 poults, were weighed, sorted, and assigned to a treatment with 8 poults per pen. In both trials, poults were fed experimental diets with the digestible lysine levels ranging from 1.08 to 1.43% in the 4 to 15 day period and 0.88 to 1.30% in the 29 to 40 day period. The experiments were of a complete randomized block design with eight treatments and six replicates per treatment. The highest level of lysine received three treatments at the expense of the positive control groups, which were fed a standard corn, soybean meal, and porkmeal diet based on the NRC (1994) requirements. Experimental data were analyzed by analysis of variance and splined regression analysis. Digestible lysine requirement based on splined regression analysis for the 4 to 15 day period were found to be 1.29% for body weight gain. For the 29 to 40 day growth period, the digestible lysine requirement was determined to be 1.16% for body weight gain and 1.12% for feed conversion.